Intertextual Pointers in the Text Alignment Network - Kalvesmaki, Joel (Journal of data mining and digital humanities, 2017)
The Text Alignment Network (TAN) is a suite of XML encoding formats intended to serve anyone who wishes to encode, exchange, and study multiple versions of texts (e.g., translations, paraphrases), and annotations on those texts (e.g., quotations, word-for-word correspondences). This article focuses on TAN’s innovative intertextual pointers, which, I argue, provide an unprecedented level of readability, interoperability, and semantic context. Because TAN is a new, experimental format, this article provides a brief introduction to the format and concludes with comments on progress and future prospects.